Age as Consumption Factor in Morphine Patient-Controlled Analgesia (PCA) for Knee Ligamentoplasty - Laouamri, Okba (HM Publisher, 2023)
Introduction: The consumption of morphine, or any other opioid analgesic, can be influenced by various factors, including age and sex. These factors play important roles in how individuals respond to and metabolize opioids, which can have implications for their pain management and potential risks associated with opioid use. The study was to investigate the relationship between age and total morphine consumption during knee ligamentoplasty with the use of three analgesic techniques. Methods: The study included 165 patients undergoing primary reconstruction of the anterior cruciate ligament of the knee. All patients underwent spinal anaesthesia. The first group, systemic analgesia (SA), received balanced systemic analgesia postoperatively for a minimum of five days, based on Paracetamol, Diclofenac and a morphine PCA. In addition to the systemic analgesia already described, the second group, femoral analgesia (FA), will benefit from a femoral peri-nervous catheter in the crural position. 20 ml of bupivacaine at 0.125% concentration is injected; maintenance is set up immediately with a continuous flow of 8 ml/h for 36 h. The third intra-articular analgesia (IAA) group received, in addition to the same systemic analgesia, an infusion through an epidural catheter of 20 ml of 0.125% bupivacaine, followed by maintenance with 8 ml/h of the same local anesthetic via an electric syringe pump for 36 h. Results: Cumulative morphine consumption was assessed, as was pain at rest using a numerical scale (EN) from 1 to 10. Data were collected from H0 to H36. Overall consumption was 15.13 ± 12.35 mg. The difference in consumption was not significant according to gender and ASA, but it was significant according to mean age. There was a negative correlation between age and morphine consumption, with Pearson's R at -0.19 p 0.016. Conclusion: Morphine consumption kinetics follow those of post-operative pain and its intensity, but also of other factors, including the patient's age. Young age is one of the criteria for over-consumption of morphine.